1972
DOI: 10.1021/jo00972a031
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of the second dissociation constants of the aminoisoquinolines

Abstract: ide ion at phosphorus. By analogy to these and other studies the mechanism that is occurring in the basic re-gion (above pH 9) is attack of hydroxide ion with the probable formation of a pentacoordinate intermediate (the formation of this intermediate has not been unambiguously established in the alkaline hydrolysis of noncyclic phosphorus compounds).The high rate of reaction of 1 may be simply a more rapid rate due to the phosphorus atom being more liable to attack because of the lack of steric hindrance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Reference 16. 4-Amino-1,6-naphthyridine. This isomer was used as previously prepared:24 NMR (CF3C02D) (external Me4Si) 9.73 (s, 5-H), 8.49 (d, 7-H), 8.06 (d, 2-H), 7.97 (d, 8-H), 6.38 (d, 3-H), J2,3 ~7.0, e/7^-7.0 Hz.…”
Section: Spectrophotometric Determination Of the Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference 16. 4-Amino-1,6-naphthyridine. This isomer was used as previously prepared:24 NMR (CF3C02D) (external Me4Si) 9.73 (s, 5-H), 8.49 (d, 7-H), 8.06 (d, 2-H), 7.97 (d, 8-H), 6.38 (d, 3-H), J2,3 ~7.0, e/7^-7.0 Hz.…”
Section: Spectrophotometric Determination Of the Dissociationmentioning
confidence: 99%
“…It was previously shown that the ultraviolet spectra of the isolated dications of the aminoquinolines and aminoisoquinolines strongly resemble the quinolinium and isoquinolinium ions, respectively. 3,4 This suggests that the final site of protonation is the primary amine group of these two isomers with the second proton being added at the second ring nitrogen atom-N-l.…”
mentioning
confidence: 99%
“…For example, 123 reacts with phosphoryl chloride to give 307 (Scheme 17.168) [470]. [471] or spectrophotometry [472]. The most basic aminoisoquinoline bearing the amino group on the benzene ring is the 6-isomer 351; the high basicity is due to its most stable resonance contribution, that is, a para-quinoid structure.…”
Section: Electrocyclic and Photochemical Reactionsmentioning
confidence: 99%
“…Isoquinoline and its derivatives widely exist in nature and many drugs contain isoquinoline structural units, which have complex structural types and a variety of biological activities. For example, many compounds have the effects of analgesia, anesthesia, anti-inflammation, anti-cancer, hypoglycemia, and hypotension. Isoquinoline derivatives are widely used in medicine, pesticides, and other fields, which has been attracting more and more attention about their synthesis routes and further applications. Consequently, the biological activity of isoquinoline derivatives has aroused the interest of researchers, who have reported the synthesis methods of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the biological activity of isoquinoline derivatives has aroused the interest of researchers, who have reported the synthesis methods of these compounds. However, most of these methods use toxic, flammable, or nonrecyclable reagents as reaction solvents …”
Section: Introductionmentioning
confidence: 99%